Sedation and analgesia in post-cardiac arrest care: a post hoc analysis of the TTM2 trial - Ceric, Ameldina; Dankiewicz, Josef; Cronberg, Tobias; Düring, Joachim; Moseby-Knappe, Marion; Annborn, Martin; May, Teresa L; Thomas, Matthew; Grejs, Anders Morten; Rylander, Christian; Belohlavek, Jan; Wendel-Garcia, Pedro; et al. (Critical care (London, England), 2025)
BACKGROUND: The routine use of sedation and analgesia during post-cardiac arrest care and its association with clinical outcomes remain unclear. This study aimed to describe the use of sedatives and analgesics in post-cardiac arrest care, and evaluate associations with good functional outcome, survival, clinical seizures, and late awakening. METHODS: This was a post hoc analysis of the TTM2-trial, which randomized 1900 out-of-hospital cardiac arrest patients to either normothermia or hypothermia. In both groups, deep sedation (Richmond Agitation and Sedation Scale ≤ -4) was mandatory during the 40-h intervention. Cumulative doses of sedatives and analgesic drugs were recorded within the first 72 h from randomization. Outcomes were functional outcome (modified Rankin Scale) and survival status at 6 months, occurrence of clinical seizures during the intensive care stay, and late awakening (Full outline of unresponsiveness motor score of four 96 h after randomization). Cumulative propofol doses were divided into quartiles (Q1-Q4). Logistic regression models were used to assess associations between sedative doses and functional outcome and survival, clinical seizures, and late awakening, adjusting for the severity of illness and other clinical factors influencing sedation. RESULTS: A total of 1861 patients were analyzed. In a multivariable logistic regression model, higher propofol doses (Q3, 100.7-153.6 mg/kg) were associated with good functional outcome (OR 1.62, 95%CI 1.12-2.34) and (Q2 and Q3, 43.9-153.6 mg/kg) with survival (OR 1.49, 95%CI 1.05-2.12 and OR 1.84, 95%CI 1.27-2.65, respectively). Receiving fentanyl and remifentanil were associated with good functional outcome (OR 1.69, 95%CI 1.27-2.26 and OR 1.50, 95%CI 1.11-2.02) and survival (OR 1.80, 95%CI 1.35-2.40 and OR 1.56, 95%CI 1.16-2.10). Receiving fentanyl (OR 0.64, 95%CI 0.48-0.86) and higher propofol doses (Q2-4 (43.9-669.4 mg/kg) were associated with the occurrence of clinical seizures. The highest quartile of propofol dose (153.7-669.4 mg/kg, OR 3.19, 95%CI 1.91-5.42) was associated with late awakening. CONCLUSIONS: In this study, higher doses of propofol and the use of remifentanil and fentanyl were associated with good functional outcome and survival, occurrence of clinical seizures, and late awakening.
Keywords: Sedation; logistické modely; analgezie; hypnotika a sedativa; Female; Seizures; Targeted temperature management; Hypnotics and Sedatives; Analgesics; ženské pohlaví; Logistic Models; hluboká sedace; Propofol; Out-of-Hospital Cardiac Arrest; lidé; Cardiac arrest; zástava srdce mimo nemocnici; Deep Sedation; Male; propofol; Aged; analgetika; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Analgesia; Midazolam; Humans